Industrial Semi-Solid Rheocasting of Aluminum A356 Brake Calipers - U. A. Curle; J. D. Wilkins; G. Govender (Advances in Materials Science and Engineering)
Industrial semi-solid casting trials of aluminum A356 brake calipers were performed over five days with the CSIR-RCS and high-pressure die casting process cell. Consecutive visual passed castings were used as the measure of process stability, and common defects between trials were categorized. Short fill results are erratic and caused by unintended underdosing by the furnace or incomplete billet discharge at the delivery point in the shot sleeve. Cold shuts can be significantly reduced by adjusting the shot control profile. Surface finish defects include surface roughness and staining caused by lubricant burn off. Visual passed castings display none of the above-mentioned external defects. X-ray examination and pressure testing of heat-treated castings from the consecutive visual passed castings show improvement over the five days. These initial-stage industrialization efforts pave the way for process commercialization.